Clinical significance of sarcopenic dysphagia for patients with esophageal cancer undergoing esophagectomy: A review - Junya Oguma; Soji Ozawa; Koshiro Ishiyama; Hiroyuki Daiko (Annals of Gastroenterological Surgery, 2022)
Abstract The relationships among esophagectomy for esophageal cancer, dysphagia, and sarcopenia are still unclear. We considered appropriate interventions for patients with resectable esophageal cancer for the purpose of reducing postoperative dysphagia and aspiration pneumonia. Dysphagia in patients with esophageal cancer is caused by patient characteristics, such as pathophysiology and age, or complications after esophagectomy. Recently, sarcopenic dysphagia, defined as dysphagia associated with whole‐body sarcopenia, has attracted attention in various fields, and a large proportion of patients with esophageal cancer are expected to have sarcopenic dysphagia. Our systematic review and meta‐analysis suggested that preoperative sarcopenia in patients with esophageal cancer is related to pulmonary complications after esophagectomy, and some reports also suggested that sarcopenia in swallowing‐related muscles, such as the geniohyoid muscle and tongue, might be associated with postoperative pneumonia or dysphagia after esophagectomy. However, clinical studies on sarcopenic dysphagia in patients with esophageal cancer have been limited. To prevent sarcopenic dysphagia after esophagectomy, perioperative interventions involving not only swallowing rehabilitation, but also physical exercise and nutritional support are important. Moreover, several reports have suggested that the chin‐down maneuver might be effective for preventing aspiration after an esophagectomy. To inhibit the progression of sarcopenic dysphagia after esophagectomy, evaluations and interventions by multidisciplinary staff are likely to be necessary.